Literasi Digital dalam Memediasi Pengaruh Transformasi Digital terhadap Peran Akuntan Manajemen - Syacita Sheril Putri Wila; I Komang Arthana; Filipus Argentano Guntur Suryaputra (AKUNTANSI 45, 2025)
This study aims to determine the role of digital literacy in mediating the influence of digital transformation on the role of management accountants among students of the Accounting Study Program, Faculty of Economics and Business, University of Nusa Cendana. This study applies a quantitative approach, with data collected through questionnaires completed by respondents. The sample consisted of 100 students from the Accounting Study Program, selected using a random sampling method. Data analysis was conducted using the Partial Least Square (PLS) method with the SmartPLS 3.0 application. The direct test results show that digital transformation has a positive and significant effect on both digital literacy and the role of management accountants. Digital literacy also has a positive and significant effect on the role of management accountants. The indirect test results reveal that digital literacy is proven to significantly mediate the relationship between digital transformation and the role of management accountants.